Religion in the national agenda what we mean by religious, spiritual, secular - Sommerville, C. John (Charles John) 1938- (Texas Baylor University Press, 2009)
C. John Sommerville examines common linguistic uses of the terms "religion," "religious," "spiritual," and "secular" in order to discern the proper use of these words in contemporary American culture. For example, he finds that, in English, "religion" is our word for a certain kind of response to a certain kind of power (the power and the response both being beyond anything else in our experience). Sommerville then redeploys these definitions to examine the ways that institutions in the fields of education, science, law, politics and religion are affected-often in unexpected ways-by a shared set of assumptions about what these words mean--From publisher description
Growing confusion over religion and spirituality -- Defining "religious" and "religion" -- Why religion and education challenge each other -- Religion and the law -- Religion and political variety -- Science and reductionism -- Sciences of human life -- Religion and theologies at odds -- What we mean by secular
Includes bibliographical references (pages 205-234) and index
Keywords: Religion; Spirituality; Secularism; Religion and science; Religion and politics